ANALISIS DETERMINAN PEMBANGUNAN DESA DENGAN MENGGUNAKAN PENGELOLAAN ALOKASI DANA DESA (ADD) STUDI PADA DESA TEGAL TUGU GIANYAR - Triadhi, Nyoman Andika (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2022)
This study aims to determine the most influential factors on village development by utilizing the Village Fund Allocation (ADD). The population in this study is the Perbekel, Village Apparatus, Village Consultative Body (BPD) and other community leaders who play an important role in Village Development. The sample in this study amounted to 41 people using the full sampling method. This type of research is quantitative, with classical assumption test, determination test, multiple linear test, partial significance test (t-test), simultaneous significance test (F-test) and validity and reliability tests are carried out. The results of the study show that the influence of community participation, transparency and accountability in managing village fund allocations partially and simultaneously has a positive and significant effect on village development.